2013
DOI: 10.3329/ujzru.v31i0.15372
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan parasites in a wastewater treatment plant of Bangladesh

Abstract: Parasitic infection is a global health problem especially in developing countries. Municipal wastewaters always contain cysts of parasitic protozoans at some level. The present study was conducted to detect protozoan parasites in different stages of the treatment plant to check its efficacy. Wastewaters were collected from 3 points of the Pagla Sewage Treatent Plant (PSTP) of Dhaka, Bangladesh, throughout the year, 2007-08 at fortnight intervals. Giardia spp., Entamoeba spp., Entamoeba coli, Endolimax nana, Id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Microscopic observations revealed the presence of protozoan parasite Giardia in sewage water. Also, Entamoeba coli, Endolymax nana, Iodoamoeba butschlii and Balantidium coli were found (Khanum et al 2011).…”
Section: Resultsmentioning
confidence: 97%
“…Microscopic observations revealed the presence of protozoan parasite Giardia in sewage water. Also, Entamoeba coli, Endolymax nana, Iodoamoeba butschlii and Balantidium coli were found (Khanum et al 2011).…”
Section: Resultsmentioning
confidence: 97%
“…Similarly to raw untreated wastewater the treated one may pose the same though reduced risk for water and the environment (Slifko et al, 2000). For example, Khanum et al (2012) observed the presence of protozoa in municipal wastewater from wastewater treatment plants and confi rmed their survival ability during treatment processes. Analysis of treated wastewater validated the presence of protozoa such as Giardia spp., Entamoeba spp., Entamoeba coli, Endolimax nana, Idoamoeba butschlii, and Balantidium coli.…”
Section: Discussionmentioning
confidence: 99%
“…The transmissive stage of G. duodenalis is a dormant cyst (Adam, 2001) and infection, known as giardiasis, can cause acute diarrhea, abdominal pain, nausea, malabsorption, and weight loss (Fletcher et al, 2012). Other pathogenic protozoa, including Cyclospora, Entamoeba histolytica (which causes amoebic dysentery), Isospora belli, and Enterocytozoon bieneusi, have also been reported in outbreaks of waterborne illness (Khanum et al, 2013).…”
Section: Protozoamentioning
confidence: 99%